First-Year EFL Students' Attitudes Toward Higher Education Reform in Morocco: Confidence, Concerns, and the Theory of Planned Behavior - Ilias Boumassaoudi; Fouad Zahouani (Jurnal Educatio FKIP UNMA, 2025)
Higher education systems globally are undergoing transformative reforms to align with evolving labor market demands and competency-based frameworks. Morocco's recent pedagogical reform, implemented in 2023, emphasizes skills development, digital literacy, and employability, yet student perspectives on these changes remain underexplored. This cross-sectional quantitative study examined first-year English as a Foreign Language students' attitudes toward the reform at the University of Al Quaraouiyine. Using a Theory of Planned Behavior framework, a 24-item Likert-scale questionnaire assessed 217 students across four dimensions: anxiety, confidence, liking, and perceived usefulness. Data were analyzed using descriptive statistics in SPSS. Students demonstrated generally positive attitudes (M = 3.97, SD = 0.58), characterized by high confidence (M = 4.15) and low anxiety (M = 4.12). However, 73.3% expressed concern regarding the removal of the Final Year Project, fearing diminished educational quality and reduced research-career preparation. Additionally, 32.7% remained neutral about the reform's job-market value, reflecting uncertainty about tangible employability outcomes. The findings indicate early reform acceptance among first-year students, yet highlight critical concerns requiring institutional attention. The removal of capstone research experiences threatens research socialization and academic depth, while job-market uncertainty undermines perceived reform legitimacy. Institutions must balance employability objectives with research opportunities, strengthen employer partnerships, and provide transparent graduate outcome tracking to sustain student confidence and engagement throughout the reform implementation process.